DETERMINAN KECEPATAN PERUBAHAN STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - , Freddy Nemesius Wetty, SE; , Prof. Dr. Eduardus Tandelilin, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to find the determinants of the speed adjustment of capital structure in Indonesia. In addition, in this study will be discussed when the company had to make adjustments to its capital structure. Based on the trade-off theory, capital structure adjustment will lead to an optimal capital structure, therefore we need a model to determine the optimal capital structure. In this study, the characteristics of the company's consisting of variables fixed assets, firm size, firm growth and profitability are used as determinants of optimal capital structure. The study was conducted at manufacturing company in Indonesia, which is the data taken from 2001 to 2011 . In this study, the partial adjustment model ( PAM ) are used to determine the speed of adjutment in the capital structure for each company . This model will be able to capture the dynamism of the variables that affect the optimal capital structure , so that the resulting optimal capital structure will be better than previous empirical studies. After finding the optimal capital structure, the speed of each of these companies will be regressed with variable firm size, firm growth, profitability, distance, inflation and Gross Domestic Product (GDP). The results of this study show that the adjustment of capital structure in a manufacturing company in Indonesia is influenced by growth, distance, inflation and Gross Domestic Product (GDP). Increased growth of the company, distance, and GDP would result in a decrease in the speed of capital structure adjustment. In the other side inflation variable is positively correlated to the speed of capital structure adjustment.